Initial transport and turbulence analysis and gyrokinetic simulation validation in NSTX-U L-mode plasmas. (12th April 2019) - Guttenfelder, W.; Kaye, S.M.; Kriete, D.M.; Bell, R.E.; Diallo, A.; LeBlanc, B.P.; McKee, G.R.; Podesta, M.; Sabbagh, S.A.; Smith, D.R.
Abstract: Transport analysis, ion-scale turbulence measurements, and initial linear and nonlinear gyrokinetic simulations are reported for a transport validation study based on low aspect ratio NSTX-U L-mode discharges. The relatively long, stationary L-modes enabled by the upgraded centerstack provide a more ideal target for transport validation studies that were not available during NSTX operation. Transport analysis shows that anomalous electron transport dominates energy loss while ion thermal transport is well described by neoclassical theory. Linear gyrokinetic GYRO analysis predicts that ion temperature gradient (ITG) modes are unstable around normalized radii ρ   =  0.6–0.8, although E   ×   B shearing rates are larger than the linear growth rates over much of that region. Deeper in the core ( ρ   =  0.4–0.6), electromagnetic microtearing modes (MTM) are unstable as a consequence of the relatively high beta and collisionality in these particular discharges. Consistent with the linear analysis, local, nonlinear ion-scale GYRO simulations predict strong ITG transport at ρ   =  0.76, whereas electromagnetic MTM transport is important at ρ   =  0.47. The prediction of ion-scale turbulence is consistent with 2D beam emission spectroscopy (BES) that measures the presence of broadband ion-scale fluctuations. Interestingly, the BES measurements also indicate the presence of bi-modal poloidal phase velocity propagation that could be indicative of two different turbulence types. However, in the region between ( ρ   =  0.56, 0.66), ion-scale simulations are strongly suppressed by the locally large E   ×   B shear. Instead, electron temperature gradient (ETG) turbulence simulations predict substantial transport, illustrating electron-scale contributions can be important in low aspect ratio L-modes, similar to recent analysis at conventional aspect ratio. However, agreement within experimental uncertainties has not been demonstrated, which requires additional simulations to test parametric sensitivities. The potential need to include profile-variation effects (due to the relatively large value of ρ *   =   ρ i / a at low aspect ratio), including electromagnetic and possibly multi-scale effects, is also discussed.